Pengaruh Pemberdayaan Keluarga terhadap Kemampuan Deteksi Dini Stunting - Yurissetiowati, Yurissetiowati (Journal of Medical Practice and Research, 2025)
Stunting is defined by the World Health Organization (WHO) as height (TB) or length (PB) based on age (U) less than 2 standard deviations (SD) from the median standard growth of children. The purpose of this study was to analyze the effect of family empowerment on the ability to detect and prevent stunting early. The research method was a quasi-experimental study with two groups consisting of 66 respondents recruited using purposive sampling. The family empowerment instrument used a media module, and early detection ability was measured using the Stunting Prevention Tool questionnaire, while prevention behavior was measured using stunting prevention behavior. Data were analyzed using SPSS version 21 with the Wilcoxon Signed Rank Test and Mann Whitney Test. The results showed that early detection ability and stunting prevention behavior improved in the intervention group with good categories (22.41 to 79.48 and 23.87 to 81.35, respectively). The significance test results showed that family empowerment had a significant effect on early detection ability (p = 0.001) and stunting prevention behavior (p = 0.000). Conclusion: Early detection capabilities and stunting prevention behaviors can be improved through family empowerment that specifically focuses on growth, nutritional status, knowledge, additional supplements, hygiene, and discipline in posyandu activities.